Community Empowerment Strategy Through Cultural Collaboration Counseling and Community Forest Utilization - Whulandary, Elvira; Harmain, Sasmita Gazi (International Journal of Multicultural Counseling and Development, 2024)
Forest management aimed at maximizing forestry resources and empowering local communities is the focal point of production-oriented forest management. The Wana Tekat Mandiri Farmer Group Association oversees community forests, which are primarily intended to empower local residents. However, illegal logging conducted by external parties poses a significant challenge, undermining the support of these groups for regional government initiatives in guiding the Farmer Group Association in the Boalemo District. This research adopts a descriptive qualitative approach, utilizing methods such as observation, interviews, and documentation. Findings reveal that the community development and empowerment strategy in utilizing community forests has been effectively implemented, with coaching playing a pivotal role. The coaching strategy primarily focuses on developing skills, knowledge, and attitudes to enhance the community's capacity. It is anticipated that this coaching approach will positively impact community empowerment.